Volatility spillovers and determinants of contagion: a case of BRICS equity and foreign exchange markets - Nyopa, TÅ¡episo (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2020)
This study investigates the relationship between the equity markets and foreign exchange markets in Brazil, Russia, India, China and South Africa (BRICS) using Diebold-Yilmaz spillover index. The study also identifies macroeconomic fundamentals that can enhance contagion in these markets using panel dynamic ordinary least squares regressions. The study spans the period from 1997 to 2018. We find that there are interdependencies between BRICS equity markets and foreign exchange markets, except for China, whose markets are relatively isolated from other BRICS markets. Brazil is the largest contributor of volatility spillovers to other BRICS markets. The spillover indexes also indicate significant increases in volatility spillovers associated with turmoil periods in domestic and global markets. This provides evidence for contagion during crises periods. We also find that fundamental indicators and trade linkages are major drivers of increased volatility spillovers (contagion) in BRICS; and global risk indicators, such as VIX and oil prices, explain volatility spillovers in BRICS. These results hold across both equities and foreign exchange markets.
Keywords: Volatility; BRIC countries; Financial crises; Regression analysis